EXPLORING THE CHALLENGES FACED BY TEACHERS IN TEACHING WRITING SKILLS AND HOW ANCHOR CHARTS CAN ADDRESS THEM - Endarwati, Endarwati; Anwar, Khoirul; Maruf, Nirwanto (University of Kuningan, 2023)
This qualitative study explores challenges faced by teachers in teaching writing skills and evaluates the effectiveness of anchor charts in addressing them. Conducted with 20 experienced teachers from major cities in Java Island, Indonesia, through semi-structured interviews, the findings reveal common challenges, including student apathy, limited instructional time, varied abilities, organization difficulties, resource constraints, assessment struggles, and diverse genre incorporation challenges. Anchor charts emerged as a powerful instructional tool, promoting student engagement, writing organization, clarity, and coherence. Students showed increased enthusiasm and motivation, while charts facilitated improved writing structure and coherence. In conclusion, anchor charts offer a promising solution to address the challenges faced by teachers in teaching writing skills. By incorporating anchor charts in writing instruction, educators can create visually engaging and interactive learning experiences that empower students to become proficient and confident writers.The study contributes practical recommendations, aligns with cognitive process and social constructivist theories, and emphasizes the value of visual aids to foster active learning and engagement. The study suggests future research with larger samples, longitudinal and cross-cultural approaches to enrich understanding. In conclusion, anchor charts integration fosters proficient and confident writers in effective expression.